Cameron, Averil. Procopius and the six century, Duckworth (Classical Life and Letters), London 1985, XIII + 297 pp. + 4 mapas. - Ramírez de Verger, A. (Gerión. Revista de Historia Antigua, 1988)
Sin resumen